Pemanfaatan Pupuk Bokashi Bagi Masyarakat Petani Sayur Di Kelurahan Tarus Kabupaten Kupang - Siprianus Soleman Senda; Felipus Kristianto Anabokay; Yohanes Pehan Kelen; Nunung Ardyani Faot; Oktavianus Key; Stanilaus Claudio Da Lopez; Yohana Lestari; Maria Roswita Dobe; Damiana Yosefina Seran; Maria Magdalena Kedang; Yasinta Dewi; Sebastiao De Carballo Lisu Manek; Marianus Wilfridus Sambi; Yoseph Robinson Kabu; Yuventris Algius Tani; Cornelisien F. T. Hadjon; Paulus Patrisius Dewa Pattiwua (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Organic fertilizers come directly from plant or animal sources. One type of organic fertilizer is bokashi fertilizer. Bokashi fertilizer is produced from the fermentation of organic materials such as compost and manure by utilizing the help of decomposing microorganisms such as microbes or fermenting fungi. The result is in the form of solid fertilizer and the condition has decomposed so that it contains more macro and micro nutrients which are ready to be absorbed by plant roots. The use of organic fertilizers in agriculture is in accordance with agricultural efforts in harmony with nature which is healthy and brings benefits to both the soil and also to humans. The vegetable farming community in Tarus Village is one of the producers of vegetables that are supplied to the needs of the city of Kupang. Healthy vegetables presuppose the use of organic fertilizers, not chemical fertilizers. The high level of interest in the people of Kupang City for healthy vegetables has made vegetable farmers try to adjust production to consumer demand. The training on making bokashi fertilizer is beneficial for vegetable farmers in the Tarus Village to answer the needs and health of consumers.